Cod fractions in municipal sewage - comparison of determination methods - Makowska, Małgorzata; Sowińska, Aleksandra; Spychała, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The thesis presents an overview and characteristics of three different methods for determining the fraction of organic compounds in sewage: methods according to ATV guidelines, respirometric methods and particle separation methods. The results of laboratory analyses of sewage composition carried out with each of the described methods are presented. The sewage came from the sewerage collector in Grodzisk Wlkp. The research was carried out in 7 series, from October 2013 to May 2014. The results obtained with different methods were compared using a statistical test. Differences are a consequence of conventionally accepted coefficients and ranges of particle size and errors during the manual separation of particles
Keywords: municipal sewage; organic impurity fractions; methods for determining organic impurities fraction